Using Retrieval vs. Cache Augmented Generation for a Pok´emon Chatbot - Cengiz Gunay; Jonathan Tran (Proceedings of the International Florida Artificial Intelligence Research Society Conference)
Cache Augmented Generation (CAG) can be an alternative to Retrieval Augmented Generation (RAG). There are differences between the two frameworks, but they work largely in the same way. One of the major differences between CAG and RAG is that CAG uses preloaded content rather than continuously calling to updated data as RAG does. In this poster, we will compare the performance of RAG vs. CAG approaches with an example chatbot application that can answer queries about Pok´emon.